2014
DOI: 10.1161/circinterventions.113.000738
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of a Drug-Free Early Programmed Dismantling Polylactic Acid Bioresorbable Scaffold and a Metallic Stent in the Porcine Coronary Artery

Abstract: Background-We aimed to evaluate a new drug-free fully bioresorbable lactic acid-based scaffold designed to allow early dismantling synchronized with artery wall healing in comparison with a bare metal stent (BMS). Methods and Results-Twenty-three BMS (3.0×12 mm) and 36 lactic acid-based bioresorbable scaffolds (BRS, 3.0×11 mm) were implanted in porcine coronary arteries. QCA and optical coherence tomographic analyses were performed immediately after implantation and repeated after 1, 3, and 6 months. Microcomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…We have previously reported that dismantling of the ART‐BRS occurs as early as 3 months after scaffold implantation according to micro–computed tomography 9. Early dismantling is the dominant feature of the ART‐BRS and was confirmed by OCT imaging and histopathologic assessment.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We have previously reported that dismantling of the ART‐BRS occurs as early as 3 months after scaffold implantation according to micro–computed tomography 9. Early dismantling is the dominant feature of the ART‐BRS and was confirmed by OCT imaging and histopathologic assessment.…”
Section: Discussionmentioning
confidence: 82%
“…QCA was carried out and analyzed by an independent core laboratory (AccelLAB, Montreal, QC, Canada) as previously described 9. The Medis QCA‐CMS 6.0 system (Raleigh, NC) was used for QCA measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Experimental data using a poly-dl-lactic acid drug-free BRS in a porcine model showed that a BRS displaying a rapid degradation profile (molecular weight loss ≈86% at 6 months) presented similar healing profiles compared with bare metal stent at 6 months. 17 However, clinical data suggest that rapid polymer absorption reduces radial force of the scaffold prematurely, which can lead to late recoil and adverse clinical events 18 ; moreover, in the clinical setting, a longer resorption period (6-9 months) may provide a more stable device dismantling process and better clinical outcomes. The BRS tested in the present study is made of PLLA struts of 150 µm thickness that are arranged in a zigzag helical design and had a peak circumferential radial force of ≈0.11 MPa, similar to metallic stents right after deployment.…”
Section: Discussionmentioning
confidence: 99%
“…1 This polymer has been shown to be biocompatible and well tolerated according to the results of both in vitro and in vivo studies. [5][6][7] The Igaki-Tamai stent (ITS, Kyoto Medical Planning Co., Ltd., Kyoto, Japan), which is made of PLLA, was the first BRS developed for use in humans in 2000, and it has shown promising results in coronary arteries and superficial femoral arteries (SFAs) in clinical trials. 6,8,9 This scaffold has been commercially available for treating peripheral artery disease in 15 countries of Europe since 2009.…”
Section: Introductionmentioning
confidence: 99%